A Literary Study of Bilwa (Aegle marmelos) Medicinal Plant – A Review Article - Karveti, Rekha; Mishra, Shiromani (International Research Journal of Ayurveda & Yoga, 2021)
One of the most significant plants in the medical area is Aegle marmelos, which belongs to the Rutaceae family and has therapeutic qualities. Bilwa is used to cure a variety of illnesses. This plant has existed from the beginning of time. All parts of the plant, including the fruits, leaves, bark, stem, and root, are used to cure a range of illnesses since it generates a multitude of alkaloids. Its therapeutic qualities include anti-diarrheal, anti-dysenteric, anti-pyretic, and anti-inflammatory effects. Fruit derived chemicals have showed promise in the treatment of illnesses like diabetes, stomach ulcers, and hyperlipidemia. This review paper discusses the architecture, distribution, nutritional effect, Ayurvedic uses, and pharmacological characteristics of this plant.